Generation of Plasmodium falciparum parasite-inhibitory antibodies by immunization with recombinantly-expressed CyRPA. (December 2016) - Favuzza, Paola; Blaser, Simon; Dreyer, Anita; Riccio, Guy; Tamborrini, Marco; Thoma, Ralf; Matile, Hugues; Pluschke, Gerd
Abstract Background The pathogenesis of malaria is primarily associated with blood-stage infection and there is strong evidence that antibodies specific for parasite blood-stage antigens can control parasitaemia. This provides a strong rationale for incorporation of asexual blood-stage antigen components into an effective multivalent malaria subunit vaccine. On the basis of available genome-wide transcriptomic and proteomic data, previously uncharacterizedPlasmodium falciparum open reading frames were screened for new blood stage vaccine candidates. This has led to the identification of the cysteine-rich protective antigen (PfCyRPA), which forms together with PfRH5 and PfRipr a multiprotein complex that is crucial for erythrocyte invasion. Methods Glycosylated and non-glycosylated variants of recombinant PfCyRPA were expressed and produced as secreted protein in mammalian cells. Adjuvanted formulations of purified PfCyRPA were tested to assess whether they can effectively elicit parasite inhibitory antibodies, and to investigate whether or not the glycosylation status affects antibody binding. For this purpose, two sets of PfCyRPA-specific mouse monoclonal antibodies (mAbs) have been raised and evaluated for functional activity. Results Generated PfCyRPA-specific mAbs, irrespective of the immunogen's glycosylation status, showed substantial parasite in vitro growth-inhibitory activity due to inhibition of erythrocyte invasion by merozoites. Furthermore, passive immunization experiments inP. falciparum infected NOD-scid IL2Rγ null mice engrafted with human erythrocytes demonstrated potent in vivo growth-inhibitory activity of generated mAbs. Conclusions Recombinantly expressed PfCyRPA tested as adjuvanted vaccine formulations in mice elicited antibodies that significantly inhibitP. falciparum asexual blood stage parasite growth both in vitro and in vivo. These findings render PfCyRPA a promising blood-stage candidate antigen for inclusion into a multicomponent malaria subunit vaccine.